Enhancing Customer Experience in the Hospitality Industry through Artificial Intelligence (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
The hospitality industry is continuously evolving, driven by the need to enhance  customer experience and satisfaction. Artificial intelligence (AI) has emerged  as a transformative technology that can significantly elevate service standards  in this sector. This research paper explores the multifaceted applications of AI  in the hospitality industry, focusing on its potential to revolutionize customer  service, personalize guest experiences, and optimize operational efficiency.  Key AI technologies discussed include machine learning algorithms, chatbots,  voice assistants, predictive analytics, and IoT-enabled smart rooms. Through  personalized recommendations, automated customer service, and data-driven  insights, AI enables hotels to anticipate and meet guest needs more effectively.  The implementation challenges—such as data protection issues, integrating with  current systems, and requiring staff training—are also covered in the article. The  hospitality sector may increase operational efficiency and profitability while also  improving visitor pleasure and loyalty by utilizing AI. This research attempts to  give a thorough grasp of AI’s effects on hospitality and provide tactical advice for  their effective use.
Keywords: Artificial Intelligence; Hospitality Industry; Customer Experience; Personalized Recommendations; Automated Customer Service; Data Analysis; Predictive Analytics; Smart Rooms; Revenue Management; Security; Loyalty Programs